Dynamic force effects on germination characteristics and weight vigoure index of three chickpea cultivars (Cicer ariegtinum L.) seed by using image processing - M. Soltani Kazemi; S. Abdanan Mehdizadeh; M.H. Gharineh (علوم و فناوری بذر ایران)
The aim of this researchwas to investigate the possibility of using image processing to determine the quality of seed germination after applying dynamic loads. For this purpose, mechanical damage at four levels (0.0404, 0.0808, 0.1212 and 0.1617) on three cultivars of chickpea seed (Azad, Hashem and ILC) were investigated. The study was conducted based on a completely randomized factorial design. The results showed that the ILC had the lowest electrical conductivity (12.02), the highest germination rate (10.31), the highest seedling growth (18.69), the most vigor (84.2), the maximum radicle length (13.29), radicle dry weight (0.574), hypocotyle dry weight (0.271) and the highest seedling dry weight (0.844) among other cultivars. Mean comparison of energy treatment showed that with inceasing energy level, germination quality and vigor were reduced. Then, length and area of radicle were evaluated using image processing. Based on statistical analysis, there was no significant difference between image processing and manual measurments. This shows the potential of replacement of time-consuming manual with image processing method for examination of seedling parameters